Anatomy of the parotid duct: Assessing variations of the parotid gland drainage pattern - E. Heidmann; K.J. Baatjes; J. Correia (Elsevier, 2021)
Introduction: The parotid duct drains the parotid gland, the largest of the human salivary glands. The PD receives an accessory PD from the accessory PG, a variation of the PG often mistaken for a soft tissue mass. The PD's superficial location contributes to the occurrence of iatrogenic and traumatic duct injuries. Case reports suggest that variations in the form of duplicated PDs, have resulted in clinical complications. Therefore, an observational, cross-sectional study was designed to determine the anatomical variations in the PG drainage pattern via the PD. Materials and methods: The left and right parotid regions of 20 embalmed cadavers (N = 40) at Stellenbosch University were dissected. Latex was injected into the oral papilla for better visualisation of the duct. The duct lengths were measured and classified. The anatomical variations of the PD were documented. Results: Six of the 40 parotid regions were excluded due to damage. Bilateral PD duplication was observed in one cadaver (5.88%), while the remaining 94.12% presented with single PDs. The mean duct length on the left and right sides were found to be 48.5 mm and 45.9 mm respectively. Additionally, accessory PGs were identified in 50% of cadavers. Conclusions: While rare, bilateral double PDs were identified in this sample. This highlights the importance of understanding anatomical variations of the PG drainage pattern via the PDs, including the incidence of accessory PGs, to limit the occurrence of unnecessary iatrogenic injury, such as compression of the duct causing salivary retention in the PD following a Rhytidectomy, and effectively repair traumatic duct injuries. Further research should be conducted to investigate the branching pattern of the PD within the PG.